Yoshimasa and the Silver Pavilion the creation of the soul of Japan - Keene, Donald (New York Columbia University Press, 2003)
Yoshimasa may have been the worst shogun ever to rule Japan. He was a failure as a soldier, incompetent at dealing with state business, and dominated by his wife. But his influence on the cultural life of Japan was unparalleled. According to Donald Keene, Yoshimasa was the only shogun to leave a lasting heritage for the entire Japanese people.
Includes bibliographical references (p. [167]-194) and index.
Keywords: Ashikaga, Yoshimasa, 1436-1490.